6 - On the Problematic State of Economic ‘Science’ - Keita, Lansana (Africa Development, 2021)
Economics is arguably the most important social science on account of its fundamental and valuational role in human decision-making. Accordingly, it is a fit discipline for probing analysis. In its present dominant configuration as ‘neoclassical economics’, it presents itself as a species of engineering thereby ignoring its evolutionary history. An examination of such will reveal that economics was and is most cognitively comprehensible in its guise as ‘political economy’. Economics’ transition to ‘economic science’ can be best explained by the mathematisation of the empirical world by empirical science and an ideologically derived attempt to evade the serious sociological and political implications of macroscopic political economy as was evidenced in the works of the classical political economists including Marx. The new approach was founded on an abstract and individualised decision-making with little relevance to the real world. Thus the important issues concerning human welfare, equity and the decisive role that politics plays in economic decision-making were all regarded as irrelevant to neoclassical economic theory. A now-dominant neoclassical economic theory means that it has become standard academic fare in African universities. Given the ideological role that neoclassical economics plays in the ongoing pillage du tiers monde, new and revived counter-theses are necessary for more effective economic analysis.